EFFECT OF ECONOMIC STRESS ON JOB COMMITMENT AMONG CIVIL SERVANTS IN THE POST COVID-19 ERA - Anugwara, Mabel C. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The recent Coronavirus pandemic created a significant impact on the civil service system of every society. The prolonged measures instituted to combat the spread of the virus undoubtedly impacted the employees' working commitment and instigated an unprecedented decline in workplace motivation. More so, the economic impact of the pandemic prompted a change in the socio-economic lifestyle of many employees and could be a factor in workplace commitment. Thus, the present study examined the effect of economic stress on job commitment among civil servants in the post-Covid-19 era. A convenience sample of two hundred and twenty respondents pooled from different ministries, departments, and agencies in the Enugu State civil service participated in the survey. The respondents completed a self-report measure of the economic stress scale and organizational commitment questionnaire. The simple regression analysis performed on the data demonstrated that economic stress positively predicted job commitment in the post-Covid-19 era. The finding revealed that economic stress explained 12.2% of the respondents' job commitment variation.